Análise dos efeitos da globalização monetária e financeira sobre a estrutura e o funcionamento do sistema financeiro brasileiro - Assis, Nanci Souto de (2007)
The aim of this thesis is to document the important fusion and acquisition process that was created during Real Plan, on this period at Brazil had one change in your system through the open market and the change of your cambial system. We believed that it is recent event and your documentation is very simple and generic, so we decided to create our interpretation about this subject. On the first chapter, we describing about main and important historic moments. On the next chapter, we are reviewing the economic and financial concepts through chronologic line. On the third chapter, we go to investigating how this alteration (monetary and cambial politic) to accelerate the financial structural system process. Finally, on the fourth chapter we are to exposure all numbers about the new brazilian financial structure and to context then in to the worldwide process in other words financial globalization process